Environmental DNA illuminates the dark diversity of sharks - Boussarie, G.; Bakker, J.; Wangensteen, O.; Mariani, S.; Bonnin, L.; Juhel, J.; Kiszka, J.; Kulbicki, M.; Manel, S.; Robbins, William; Vigliola, L.; Mouillot, D. (American Association for the Advancement of Science (A A A S), 2018)
© 2018 The Authors. In the era of "Anthropocene defaunation," large species are often no longer detected in habitats where they formerly occurred. However, it is unclear whether this apparent missing, or "dark," diversity of megafauna results from local species extirpations or from failure to detect elusive remaining individuals. We find that despite two orders of magnitude less sampling effort, environmental DNA (eDNA) detects 44% more shark species than traditional underwater visual censuses and baited videos across the New Caledonian archipelago (south-western Pacific). Furthermore, eDNA analysis reveals the presence of previously unobserved shark species in humanimpacted areas. Overall, our results highlight a greater prevalence of sharks than described by traditional survey methods in both impacted and wilderness areas. This indicates an urgent need for large-scale eDNA assessments to improve monitoring of threatened and elusive megafauna. Finally, our findings emphasize the need for conservation efforts specifically geared toward the protection of elusive, residual populations.